Penggunaan Agens Hayati Pseudomonas fluorescens terhadap Pertumbuhan Tanaman Kedelai (Glycine max L. Merr,) - wuryantoro wuryantoro; Wuye Ria Andayanie; Ndaru Hadian Dhuhava (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2021)
Abstract—Soybean (Glycine max L.) is the third most important food commodity after rice and corn in Indonesia. This study aims to determine the interaction of soybean growth that has been incubated using Pseudomonas fluorescens. The research method used a randomized block design experiment consisting of five treatments, namely S1 (soybean seeds were given Pseudomonas fluorescens and not incubated), S2 (soybean seeds were given Pseudomonas flourescen and incubated for 6 hours), S3 (soybean seeds were given Pseudomonas flourescens and incubated for 12 hours), S4 (soybean seeds were given Pseudomonas flourescens and incubated for 18 hours), and S5 as a control. The test used univariate analysis and further tested with Duncan's test with a level of 5%. The results showed that there was no significant effect on the use of Pseudomonas flourescens as a soybean seed incubation material on the parameters of plant height, leaf area, wet weight, and dry weight of soybean plants. Keywords—:Soybean; Pseudomonas fluorescens; incubation; seeds; biological agents